A strategy of antimicrobial therapy of pelvic inflammatory diseases at antibiotic resistance of microbial pathogens - Tatiana Yu Pestrikova; Elena A Yurasova; Igor V Yurasov (IP Berlin A.V., 2019)
Relevance. Antibiotic resistance of microbial pathogens is an interdisciplinary and interstate problem of major medical and socio-economic importance. If multiresistant microbial flora is detected in patients with acute or chronic forms of pelvic inflammatory diseases alternative antimicrobial combined therapy an advisability should be considered. Current trends of an increase in multiresistant gram-negative infections along with limited range of alternative treatment options dictate a need for further research. Study of alternative antibiotics effectiveness in pelvic inflammatory diseases treatment is necessary for a further development of optimal treatment regimens. Aim. To search for adequate combinations of antimicrobial therapy aimed at antibiotic-resistant pathogens. Materials and methods. To write this review a search for domestic and foreign publications in Russian and international search systems (PubMed, eLibrary, etc.) for the last 2-12 years was conducted. The review includes articles from peer-reviewed literature. Results. Fosfomycin possesses a broad spectrum of antibacterial effects including gram-positive and gram-negative aerobic bacteria. The drug is highly effective against Pseudomonas aeruginosa and Escherichia coli, anaerobic bacteria (Proteus mirabilis and Klebsiella pneumoniae) as well as against gram- positive bacteria (Staphylococcus spp., including S. aureus, S. epidermidis; Streptococcus spp., including Enterococcus faecalis). Conclusions. When multiresistant microbial flora is detected in patients with acute or chronic forms of pelvic inflammatory diseases an advisability of fosfomycin administration should be considered.